Exploring Madurese Riddles and Their Relevance in Indonesian Language Learning with Local Wisdom - Giri Indra Kharisma; Iswan Afandi (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2026)
Madurese riddles (bhâk-tebbhâghân) are part of oral tradition that function not only as entertainment but also as symbolic cultural expressions reflecting the linguistic creativity, worldview, and collective cognition of the Madurese community. However, the continuity of this tradition is increasingly threatened by modernization and shifting communication patterns among younger generations. This study aims to (1) identify the forms of Madurese riddles, (2) analyze the cultural values embedded within them, and (3) reconstruct their relevance as local wisdom-based Indonesian language learning materials. This research employed a descriptive qualitative approach using folklore and cultural linguistics perspectives. Data were collected through observation, semi-structured interviews, documentation, and literature review involving children, adult community members, a community leader, and an Indonesian language teacher in Situbondo Regency. Data analysis was conducted through data condensation, classification, interpretation, and thematic analysis. The findings reveal four dominant forms of Madurese riddles, namely metaphorical, acronymic, erotic, and deceptive riddles. Metaphorical riddles were found to be the most dominant form, indicating that the Madurese community tends to construct meaning through symbolic association and analogical reasoning rooted in everyday cultural experiences. The riddles contain sociopsychological and erotic values that reflect humor, social criticism, symbolic negotiation, and local cultural perspectives. From a pedagogical perspective, Madurese riddles are relevant to Indonesian language learning, particularly in observation report text (Laporan Hasil Observasi/LHO) learning, because they encourage inferential thinking, descriptive competence, cultural literacy, and contextual learning. This study contributes to the development of linguistic folklore and culturally responsive language learning by reconstructing oral tradition not only as a cultural artifact but also as transformative pedagogical material within Indonesian language education.